Design of ABC, Procedures Manual, EOQ, AHP and Criteria Comparison Matrix to reduce costs in a shoe manufacturing company - Alegre Martínez, Everth Sebastian (2021)
This work was prepared in order to be able to solve the problems that the company Mana Bussines S.A.C. faced, these are focused on the areas of production and logistics, these being the delays in the location of materials due to disorder in the warehouse, the presence of defective products, excess inventory, stops due to lack of material and returns of materials due to Providers. That is why there is a need to be able to provide a solution to improve the company economically. For this, engineering tools such as AHP, EOQ, Procedures Manual, ABC Classification, Criteria comparison matrix were used. All these tools were simulated showing cost reduction.